Plasmid DNA-loaded chitosan/TPP nanoparticles for topical gene delivery - ÖZBAŞ, SUNA (INFORMA HEALTHCARE, 2011)
Topical application of plasmid DNA represents an attractive route of gene delivery. Although chitosan (CS) has been widely investigated as a gene-carrier, there is very limited information about the skin application of CS-based systems for DNA. This study evaluated pDNA-loaded chitosan nanoparticles (CS-NPs) for skin gene delivery. NPs were prepared by inducing the gelation of CS upon interaction with sodium tripolyphosphate. pSV-beta-Gal was used as a reporter gene. The size, surface charge, and the other in vitro characteristics of CS-NPs were examined. Primary human dermal fibroblast cells (HDF) and mouse fibroblast NIH 3T3 cell lines (ATCC CCL-92) were used for in vitro transfection studies. In in vivo study, CS-NPs were applied to the skin of baby and adult Sprague Dawley rats by spreading on the shaved area of the back of animals. During a week animals were sacrificed and skin biopsies were taken for beta-Gal expression. beta-galactosidase enzyme activity was determined spectrophotometrically at 420 nm. The distribution of beta-galactosidase expressing cells within the skin tissue was observed by X-gal histochemical method. beta-galactosidase was continuously expressed at the nanoparticle-treated skin during the 7 days. High and continuous beta-Gal expressions were obtained with CS-NPs, although it was low in the first day. When a comparison was made between the data of baby and adult rats, markedly high transfection were measured in the skin samples of the baby rats. NPs protected pDNA against the enzyme and serum attacks. In conclusion, CS-NPs showed in vivo transfection potential in rats for skin gene delivery.
Keywords: Chitosan; DNA; nanoparticles; skin; gene delivery; gene expression; dermal; ADMINISTRATION IN-VIVO; TRANSFECTION EFFICIENCY; HAIR FOLLICLE; PARTICLE-SIZE; NAKED DNA; SKIN; THERAPY; MICROSPHERES; EXPRESSION; VITRO